POLITIK DAN BIROKRASI: MASALAH NETRALITAS BIROKRASI DI INDONESIA ERA REFORMASI - Firnas, M Adian (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
The political reforms that emerged in 1998 brought a new round of the democratic life in Indonesia, including on aspects of bu- reaucracy. Political reform demands the birth of the professional bureaucracy and free of pragmatism and political co-option by the authorities as it did in the New Order regime. The challenge to build a bureaucracy that is neutral and free from political coopta- tion getting stronger after the advent of Law No. 34 Year 2004 on the Principles of Local Government which stipulates that the local elections conducted directly.